The Effective Management of Fever in Pediatrics and Insights on Remote Management: Experts' Consensus Using a Delphi Approach - Chiappini, Elena; Vitale, Antonio; Badolato, Raffaele; Becherucci, Paolo; Careddu, Domenico; Di Mauro, Antonio; Doria, Mattia; Staiano, Annamaria (Frontiers in Pediatrics, 2022)
Background Even after the publication of the 2017 update of Italian guidelines on treatment of fever in pediatrics, some fundamental questions are still open and new ones emerged during the COVID-19 pandemic. Objective To assess the level of consensus among Italian pediatricians on different topics related to treatment of fever in children by using the Delphi technique. Methods A Delphi study was undertaken between June and September 2021, when two questionnaires were consecutively sent to a panel of experts to be answered anonymously. An invitation to participate was sent to 500 pediatricians distributed over the whole national territory and 80 (16%) of them accepted to participate on a voluntary basis. The questionnaires were structured into three specific topics: “therapeutic appropriateness and management of the febrile child,” “management of the febrile child in the presence of other diseases,” and “future perspectives in remote management.” Each topic had six statements. Results A first-round questionnaire was sent to 80 accepting pediatricians from different Italian regions. Of the 72 respondents (23% working in hospitals and 72% outside), 33% were from northern, 12% central, and 55% southern Italy or islands. A second-round questionnaire was sent to the same 80 pediatricians and 69 of them responded, without significant differences for workplaces or geographical distribution as compared with the first questionnaire. Overall, 75 participants answered at least one of the two questionnaires. All the statements on the topics of “therapeutic appropriateness and management of the febrile child” and “future perspectives in remote management” reached the predefined cut off for consensus (75% or more). Only one statement on “management of the febrile child in the presence of other diseases” did not achieve the consensus even after the second round. Conclusions Italian pediatricians agree on several aspects of treatment of febrile children and their expert opinions could support everyday decision process complementary to recommendations by regulatory agencies and guidelines.